2021
DOI: 10.1080/2162402x.2021.1896658
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tumor-infiltrating immune cells on local control rate, distant metastasis, and survival in patients with soft tissue sarcoma

Abstract: Soft tissue sarcomas (STS) are considered non-immunogenic, although distinct entities respond to antitumor agents targeting the tumor microenvironment. This study's aims were to investigate relationships between tumor-infiltrating immune cells and patient/tumor-related factors, and assess their prognostic value for local recurrence (LR), distant metastasis (DM), and overall survival (OS). One-hundred-eighty-eight STS-patients (87 females [46.3%]; median age: 62.5 years) were retrospectively analyzed. Tissue mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The critical factor determining prognosis might be the dominance of the immune-suppressive environment or the stimulatory environment. Smolle et al [ 26 ] investigated relationships between tumor-infiltrating immune cells and patient/tumor-related factors in soft tissue sarcomas and assessed their prognostic value. They found that high macrophage levels were associated with increased local recurrence risk, irrespective of margins, age, sex or B-cell level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical factor determining prognosis might be the dominance of the immune-suppressive environment or the stimulatory environment. Smolle et al [ 26 ] investigated relationships between tumor-infiltrating immune cells and patient/tumor-related factors in soft tissue sarcomas and assessed their prognostic value. They found that high macrophage levels were associated with increased local recurrence risk, irrespective of margins, age, sex or B-cell level.…”
Section: Discussionmentioning
confidence: 99%
“…Genetically, human sarcomas are classified based on the abnormalities that drive their pathogenesis, and sarcomas can be categorized into two main groups: (1) sarcomas with simple and specific chromosomal changes (often translocations) and a low mutational burden and (2) karyotypically complex sarcomas with numerous copy number aberrations and a moderate mutational burden [ 24 ]. Among these copy number-driven tumors, UPS, dedifferentiated liposarcoma (DDLPS) and—to a lesser extent—leiomyosarcoma (LMS) can exhibit durable responses to immune checkpoint inhibitors, possibly due to heterogeneity within the tumors [ 25 , 26 ]. However, translocation-associated subtypes, synovial sarcoma (SS), and MLPS tend to show mixed results [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to DDLPS, other karyotypically complex STS have a similar or lower proportion of immune-hot tumors. In contrast, studies that lack LPS subtype differentiation reported a relatively low rate of TILs in LPS compared to other STS subtypes [ 94 , 95 , 96 , 97 ]. As this observation strongly implies that the heterogeneity of LPS infiltration cannot be reflected by pooling various LPS subtypes, it should be taken into consideration for future study design.…”
Section: Lps-infiltrating Immune Cell Subsets and Their Clinical Sign...mentioning
confidence: 99%
“…While there are reports correlating high CD3 + , CD8 + , and CD4 + T cell infiltration with a significantly favorable outcome [ 100 , 101 ], others showed that high CD3 + and CD4 + infiltrates tend to predict a negative prognosis [ 102 ]. Furthermore, several studies did not find any association between T cell infiltration and patient outcome [ 95 , 96 ]. The prognostic value of high FoxP3 + Treg levels is also undefined in mixed STS cohorts (including LPS) since no impact on OS, but a negative impact on local recurrence in multivariate analysis was demonstrated [ 95 , 102 ].…”
Section: Lps-infiltrating Immune Cell Subsets and Their Clinical Sign...mentioning
confidence: 99%
See 1 more Smart Citation